Neighborhood deprivation and depression in adult twins: genetics and gene×environment interaction. Issue 4 (9th November 2016) - Strachan, E.; Duncan, G.; Horn, E.; Turkheimer, E.
Abstract : Background: Depression is a significant problem and it is vital to understand its underlying causes and related policy implications. Neighborhood characteristics are implicated in depression but the nature of this association is unclear. Unobserved or unmeasured factors may confound the relationship. This study addresses confounding in a twin study investigating neighborhood-level effects on depression controlling for genetics, common environment, and gene×environment (G × E) interactions. Method: Data on neighborhood deprivation and depression were gathered from 3155 monozygotic twin pairs and 1275 dizygotic pairs (65.7% female) between 2006 and 2013. The variance for both depression and neighborhood deprivation was decomposed into three components: additive genetic variance (A); shared environmental variance (C); and non-shared environmental variance (E). Depression was then regressed on neighborhood deprivation to test the direct association and whether that association was confounded. We also tested for a G × E interaction in which the heritability of depression was modified by the level of neighborhood deprivation. Results: Depression and neighborhood deprivation showed evidence of significant A (21.8% and 15.9%, respectively) and C (13.9% and 32.7%, respectively) variance. Depression increased with increasing neighborhood deprivation across all twins ( p = 0.009), but this regression was not significant after controlling for A and C variance common to both phenotypes ( p = 0.615). The G × E model showed genetic influences on depression increasing with increasing neighborhood deprivation ( p < 0.001). Conclusions: Neighborhood deprivation is an important contributor to depression via increasing the genetic risk. Modifiable pathways that link neighborhoods to depression have been proposed and should serve as targets for intervention and research.